FRI0472 Extra-rheumatological features are frequently associated with peripheral rheumatological features in axial spondyloarthritis and influence the choice of the anti-tnf in daily practice. an analysis of 519 patients. (15th June 2017) - Moltό, A; Etcheto, A; Gossec, L; Perrot, S; Boudersa, N; Claudepierre, P; Roux, N; Berenbaum, F; Martin, A; Sparsa, L; Coquerelle, P; Soubrier, M; et al.
Abstract : Background: Axial involvement is the predominant feature of axSpA but both extra-articular (EAM)and peripheral manifestations (including synovitis and dactylitis) can be concomitantly observed. Objectives: To evaluate whether the EAM are associated with peripheral rheumatological features in axSpA and whether these EAM influence the choice of the anti-TNF. Methods: Study design: Prospective, multicenter, cross-sectional study in France (baseline visit of the Predict-SpA trial). Patients: definite axSpA according to the rheumatologist, requiring an anti-TNF. Data collected: Past or present signs/symptoms of EAM (psoriasis, uveitis and Inflammatory Bowel disease (IBD)), peripheral (arthritis, enthesitis and dactylitis) SpA features, and the anti-TNF prescribed by the treating rheumatologist (according to usual practice). Statistical analysis: the frequency of peripheral involvement and the type of anti-TNF (e.g. monoclonal antibodies vs soluble receptor) were compared in patients with versus (vs) without EAM. Results: Of the 519 patients (females: 46%, age: 42±12 years, HLA B27 positive: 65%, X-Ray sacroiliitis: 56%, inflammation on MRI of the sacro Iliac Joint: 56%), 386 were biologic naïve. A past history or current symptoms of psoriasis, uveitis and IBD was observed in 19%, 17% and 5% respectively and a past history or current symptoms of arthritis, enthesitis and dactylitis in 27%, 54%, 11%, respectively In patients with vs without psoriasis, the % of arthritis, enthesitis and dactylitis were 40% vs 25% (p=0.004), 67% vs 50% (p=0.002) and 18% vs 10% (p=0.026), respectively In patients with vs without uveitis, the % of arthritis, enthesitis and dactylitis were 31% vs 27% (p=0.445), 57% vs 53% (p=0.200) and 13% vs 11% (p=0.772), respectively In patients with vs without IBD, the % of arthritis, enthesitis and dactylitis were 36% vs 27% (p=0.440), 68% vs 53% (p=0.180) and 21% vs 11% (p=0. 152), respectively Monoclonal antibodies were prescribed as the first biologic in 206 out of the 386 patients (53%).This percentage was 56% vs 58% and vs 52% in patients with a current presence of psoriasis vs any history of psoriasis but currently absent and vs without any history of psoriasis, respectively; p=0.785. This percentage was 100% vs nd% (n=0) and vs 53% in patients with a current attack of uveitis vs any history of uveitis but currently inactive and vs without any history of uveitis, respectively; p=0.032. This percentage was 100% vs 50% (n=2) and vs 53% in patients with a current active IBD vs any history of IBD but currently inactive and vs without any history of IBD, respectively; p=0.064. Conclusions: In this study focused on ax SpA patients, both peripheral rheumatological clinical features and EAM were frequently observed. The peripheral rheumatological manifestations were more frequently observed in case of concomitant psoriasis. Monoclonal antibodies were the preferred anti-TNF in case of a past history (even currently quiescent) of uveitis or IBD in daily practice. Acknowledgements: This study was conducted thanks to an unrestricted grant from MSD Disclosure of Interest: None declared